Faecal Micro-RNAs in Inflammatory Bowel Diseases. (14th March 2019) - Verdier, Julien; Breunig, Irene Raphaela; Ohse, Margarete Clara; Roubrocks, Silvia; Kleinfeld, Sandra; Roy, Sanchari; Streetz, Konrad; Trautwein, Christian; Roderburg, Christoph; Sellge, Gernot
Abstract: Background and Aims: Faecal biomarkers are used as indicators of disease activity in inflammatory bowel diseases [IBD], which include Crohn's disease [CD] and ulcerative colitis [UC]. Micro-RNAs [miRNAs] are small non-coding RNAs detectable in extracellular fluids and can be used as clinical biomarkers. The aim of this study was to determine if faecal miRNA composition is altered in IBD. Methods: More than 800 different human faecal miRNAs were measured in stool samples from control individuals and patients with active CD by using NanoString technology. Selected miRNAs were quantified by qRT-PCR in faeces, serum and intestinal tissue of controls [ n = 23] and patients with inactive or active CD [ n = 22, n = 22] or UC [ n = 11, n = 24] as well as patients with Clostridium difficile infection [CDI, n = 8]. Results: In total, 150 miRNAs were significantly detected in faeces from controls and patients, and multivariate analyses showed that CD patients with high disease activities had a distinct miRNA profile and that miR-223 and miR-1246 were distinct from other faecal miRNAs. In a larger cohort, active UC patients displayed significantly higher levels of miR-223 and miR-1246 than controls while patients with CDI had higher levels of faecal miR-1246 but not miR-223. No differences were noted in serum samples. Conclusions: To our knowledge, this is the first comprehensive screen of faecal miRNAs performed in IBD. Further investigation will aim to confirm these findings in a larger cohort and to understand the biological function and cellular sources of faecal miRNAs.